(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Improving the organizational structure of enterprise management is crucial for enhancing efficiency, adaptability, and competitiveness in today’s dynamic business environment. This paper explores modern approaches to organizational design, emphasizing the shift from traditional hierarchical frameworks to flexible, technology-driven, and employee-centric models. It examines the impact of globalization, digital transformation, and sustainability on restructuring efforts, highlighting the benefits of agile and hybrid structures. Key challenges, such as resistance to change and aligning structures with strategic goals, are discussed alongside strategies for successful implementation. By adopting innovative frameworks, enterprises can foster collaboration, empower employees, and achieve sustainable growth. The findings underscore the importance of continuous evaluation and adaptation to remain competitive in an ever-evolving global economy.